Effect of Coconut and Sugarcane Fiber Volume Fraction Variations on the Tensile Properties of Epoxy Matrix Composites - Fitri, Anisa; Bayu Prasetya; Muhammad Yasin Siregar; Quratul Aini; Wahyu Solafide Sipahutar; Fathar Fathan Mubina (Universitas Nusa Putra, 2025)
Materials are continually being developed for sustainable applications. Agricultural wastes such as sugarcane bagasse and coconut fiber show great potential as reinforcing agents in polymer composites. This study investigates the effect of varying volume fractions of sugarcane and coconut fibers on the tensile properties of epoxy matrix composites. Four fiber composition ratios were prepared, maintaining a total fiber volume fraction of 50% and matrix fraction of 50%, specifically: 25:25, 20:30, 10:40, and 0:50 (coconut fiber: sugarcane fiber, respectively). All fibers underwent alkali treatment using a 5% NaOH solution to improve interfacial bonding with the epoxy matrix. Composite fabrication was performed via hand lay-up, and tensile tests followed ASTM D3039 standards using a Universal Testing Machine (UTM). The results indicated that the composite with 20% coconut fiber and 30% sugarcane fiber (sample B) exhibited the highest tensile strength of 30.48 MPa and the highest elastic modulus of 2.29 GPa, albeit with a low strain at failure (0.01), suggesting brittle behavior. In contrast, the balanced composition (25:25) demonstrated more stable mechanical performance, achieving a tensile strength of 28.31 MPa and a higher strain of 0.04, indicating improved toughness. The lowest tensile strength, 15.56 MPa, was observed in the 10:40 composition (sample C). Failure analysis revealed modes such as matrix cracking, fiber-matrix debonding, and fiber pull-out, which varied according to fiber composition. In conclusion, this study demonstrates that a balanced volume fraction of coconut and sugarcane fibers yields epoxy composites with optimal tensile strength and a favorable balance between strength and toughness.